The Sitting Position in Neurosurgery: A Clinical Study in 30 Cases (Bangladesh Journal of Neuroscience, 2013)
Objective: Sitting position for operation of posterior fossa lesions, occipital and posterior parietal lesions, foramen magnum, upper cervical spinal lesions provides an excellent visualization because of slack of brain due to gravity drainage of CSF and blood. Hence gross total tumour removal relatively easy and less complicative.Methods: From January 2008 to march 2010 total 30 cases underwent neurosurgical procedure in sitting position. Physical characteristics including patients age, sex, size of the tumour and histological diagnosis were collected. The post operative image were studied to see the extent of tumour removal and early detection of complications. Almost all patients required peroperative cerebral venous line or peripheral inserted central venous line, precordial doppler sound, ETCO2, O2 saturation and close monitoring of blood pressure.Results: Venous air embolism were detected in two cases (6.6%). Total tumour removal was possible in 17 (56.6%) cases and subtotal in 11 (36.6%) cases. There were 4 (13.33%) mortality in thirty cases, two cases from CP angle tumour and another case from petroclival meningioma and another from pineal region tumour. There was pneumocephalus in almost all cases and post-operative new facial paresis in 10 (33.3%) cases. Fifth cranial nerve palsy developed in 3 (10%) cases. Temporary lower cranial nerve palsy developed in 2 cases. Post-operative tumour bed haematoma developed in 4 (13.33%) cases. Most of the patient had good outcome (GOS 5).Conclusion: Sitting position can be safely done with good preoperative physiological, peroperative close monitoring of the patient regarding blood pressure, ETCO2 and oxygen saturation. However postoperative complication like tumour bed haematoma, pneumocephalus, cranial nerve palsy have to be bring in mind.Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 45-51